The effect of the visual exercise environment on the response to psychological stress: a pilot study. Issue 6 (1st November 2020) - Wood, Carly; Flynn, M.; Law, R.; Naufahu, J.; Smyth, N.
ABSTRACT: Background: Performing physical activity whilst exposed to nature can improve health. However, there is little evidence of its impact on stress outcomes. The aim of this study was to examine the influence of the visual exercise environment on the response to a psychosocial stressor. Methods: Eighteen participants were randomized to one of three conditions: i. nature; ii. built or; iii. control condition. Participants exercised for 30 min on a treadmill at 50% of their VO2 max whilst viewing a video of either a natural or built environment or a blank screen. Following the exercise, participants completed the Trier Social Stress Test (TSST), a standardized laboratory stressor. Salivary samples were collected before, during and after the TSST to calculate cortisol reactivity and recovery. Results: One-way ANOVA revealed a significant effect of viewing condition on cortisol reactivity [ F (2, 11)  = 4.686, p  = .034; n 2 p   = .460]; with significantly lower reactivity in the built compared to the nature condition ( p  = .027, d =  1.73). There was no effect of condition on cortisol recovery ( p  = .137; n 2 p  = .257). Conclusions: In the context of the adverse health impact of lower (i.e., blunted) cortisol responding, these findings could indicate a negative impact of the built environment on stress responses.